Penerapan Metode Promethee Pada Rekomendasi Prasarana Aset Irigasi - A'an Cun; Widodo Saputra; Hendry Qurniawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Irrigation is the use of water in agriculture to divide water into agricultural land, this is one of the factors that support the success of plant productivity. The success rate of implementing the irrigation function is measured from the performance of the existing irrigation system, so it is necessary to conduct an irrigation performance assessment. Performance appraisal based on Permen PU No. 32/2007 is carried out on 6 (six) parameters, namely; Physical Infrastructure, Planting Productivity, Supporting Facilities, Personnel Organization, Documentation and Water User Farmer Association (P3A). Currently, performance appraisal still depends on the experience of field officers or observers. For that we need a method that can measure the performance assessment of irrigation networks. One method that can be used to assess the performance of irrigation networks is by using the Promethee method which aims to reduce subjectivity with the method used by the center which is based on the PUPR Regulation No. 12 / PRT / M / 2015 concerning Guidelines for Exploitation and Maintenance of Irrigation Networks. The input data used is secondary data from the results of the irrigation network performance assessment in 2017 in several Irrigation Areas which still cover the work area of the Irrigation Management UPT Bah Bolon, Dinas Sumber Daya Air, Cipta Karya and Tata Ruang in Sumatera Utara province. The final results of the tests carried out on 14 alternatives and 6 criteria show that the alternative DI. Bah Kapul (179 Ha) (Code A005) is in the first rank with the highest net flow value of 0.9048 while the 14th or last rank is occupied by the alternative DI. Javacolonisasi / Purbogondo (1,030 Ha) (Code A009) with a net flow value of -1.4286.